Solubility and hydrolysis of U(VI) in 0.5 mol/kg NaCl solutions at T = 22 and 80 °C. (May 2018) - Endrizzi, Francesco; Gaona, Xavier; Marques Fernandes, Maria; Baeyens, Bart; Altmaier, Marcus
Graphical abstract: Highlights: Solubility and hydrolysis of U(VI) in NaCl 0.5 mol/kg at T = 22, 80 °C. A thermodynamic solubility model in the alkaline pH range is proposed. Characterization of the phases to assess the temperature effect on their stability. Abstract: In this study, the solubility and hydrolysis of U(VI) was investigated at elevated temperature. Experiments were performed in solutions of NaCl 0.51 mol/kg of water in the pHm range 4–13.4 (with pHm  = –log[H + ]) at T  =  22 ± 3 and 80  ±  5 °C under N2 /Ar atmosphere. Two solid phases were used as starting U(VI) materials: UO3 ·2H2 O(cr) equilibrated in solutions with 4 ≤ pHm  ≤ 5 and Na2 U2 O7 ·H2 O(cr) (a synthetic clarkeite-like phase) equilibrated in solutions with 7 ≤ pHm  ≤ 13.4. The solubility of UO3 ·2H2 O(cr) at T  = 80 °C in the acidic pHm -range is decreased by a factor of ten with respect to the U(VI)-phase studied at room temperature. Solid phase characterization by XRD, SEM–EDS and quantitative chemical analysis indicate that this decrease is correlated to the transformation of UO3 ·2H2 O(cr) into a sodium-containing U(VI) solid phase. The solubility of Na2 U2 O7 ·H2 O(cr) in the alkaline pHm -range is drastically enhanced at T  = 80 °C. The main contribution to this effect results from the increased acidity of water at elevated temperature, although an enhanced hydrolytic activity of U(VI) or a decreased stability of Na2 U2 O7 ·H2 O(cr) are also considered, in order to explain the solubility data under these experimental conditions. Solid phase characterization after completing the solubility experiments confirms that Na2 U2 O7 ·H2 O(cr) retains its stoichiometry and structure at T  = 80 °C within the timeframe of the study ( t  ≤ 290 days). A thermodynamic model, comprising conditional stability constants and enthalpy data has been developed, describing reliably the processes of hydrolytic dissolution of Na2 U2 O7 ·H2 O(cr) in alkaline NaCl solutions up to 0.51 mol/kg and their temperature dependence in the range 22–80 °C. This work represents the first comprehensive study on U(VI) solubility and hydrolysis at elevated temperatures extending to alkaline pHm conditions relevant in the context of nuclear waste disposal. It provides robust solubility upper limits to be considered in source term estimations, but also thermodynamic data for both solid phases and aqueous species that can be implemented in thermodynamic databases and related geochemical calculations.